Measurement of Accountability Management of Village Funds - Anggraeni Yunita; Mrs Christianingrum (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
The purpose of this study is to measure the accountability of village funds management in Kabupaten Bangka. In relation to the Village Funds program which is a government program, the measurement of accountability of Village Funds management uses accountability principles consisting of Transparency, Liability, Controlling, Responsibility and Responsiveness which are the principles of accountability developed by the United Nations Development Program in measuring bureaucratic accountability. This research is a qualitative research by taking data from several villages in Bangka Regency. As well as qualitative research, the data taken in this study using snowball sampling method, where researchers take data by conducting in-depth interviews until the data obtained until the condition is saturated, meaning there is a repetition of the same information at the time of data collection. The results of this study indicate that villages in Bangka Regency have met the accountability principles of 5 (five) starting from planning, implementation and reporting when measured from 5 (five) accountability principles consisting of Transparency, Obligation, Controlling, Responsibility and Responsiveness.